Stressful life events and current psychological distress are associated with self-reported hypertension but not with true hypertension: results from a cross-sectional population-based study - Fuchs Flávio D; Moreira Leila B; Fuchs Sandra C; Sparrenberger Felipe (BMC, 2008)
Abstract Background The evidence linking stress to hypertension has been scarcely documented in population-based studies. Methods Participants were selected through a multi-stage probability sampling and interviewed at home, being submitted to measures of demographics, anthropometrics, blood pressure (BP), and risk factors for hypertension. Hypertension was defined as BP ≥ 140/90 mm Hg or use of BP-lowering drugs or as self-reported hypertension. Stressful life events were investigated through an inventory of nine major life events occurring in the year preceding the interview. Psychological distress was evaluated through a facial scale of expression of emotion in the last month. Results In the total, 1,484 adult individuals were investigated. Prevalence of hypertension was lower in individuals who reported any stressful life event in comparison with individuals who did not reported an event (34.3 versus 44.2%, P < 0.01), such as relative or friend death, loss of job, divorce, violence and migration. There was a trend for higher prevalence of hypertension in individuals with higher psychological distress in the last month, which was not longer significant after adjustment for confounding. In contrast, individuals who self-reported hypertension, but actually had normal blood pressure and were not using antihypertensive medication, reported higher numbers of stressful events. Conclusion Recent stressful life events and current psychological distress are not associated with hypertension. Associations between stress events and distress with self-reported hypertension are not intermediated by effects of stress on blood pressure, and may be ascribed to negative feeling about disease and not to the disease itself.